RESPON PERTUMBUHAN DAN BIOKIMIA MICROGREENS TANAMAN BASIL (Ocimum basilicum L.) TERHADAP KOMBINASI WARNA LED DAN LAMA PENYINARAN YANG BERBEDA - Endah Nugraheni; Karno Karno; Sutarno Sutarno (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Microgreen is a functional food crop that aims to create a globally sustainable food diversification with high nutritional value compared to ordinary plants. Basil is one type of plant that is often used as a microgreen because of it is complete nutritional content. Increasing the production and quality of microgreens can be done by providing LED lighting with the required light spectrum and increasing the duration of irradiation. The aim of this study was to examine the growth and biochemical response of microgreens bacilli to the combination of red, blue, and red:blue LEDs and the duration of irradiation for 12, 16 and 20 hours. The research was carried out on April 2021 - May 2021 at the Plant Ecology and Production Laboratory and the analysis of chlorophyll, carotenoids and phenols was carried out at the Laboratory of Physiology and Plant Breeding, Faculty of Animal and Agricultural Sciences (FPP), Diponegoro University. The experimental design used in this study was a completely randomized design (CRD) with a factorial pattern of 5 x 3 with 3 replications, so there were 45 experimental units. The first factor was the LED color combination which includes L1: 100% Red: 0% Blue, L2: 0% Red: 100% Blue, L3: 70% Red:30% Blue, L4: 50% Red: 50% Blue, L5: 30 %Red:70%Blue. The second factor was the length of irradiation including T1 (12 hours), T2 (16 hours), T3 (20 hours). Based on the research conducted, it can be concluded that there was an interaction between the combination of light color and the duration of irradiation on the biochemical content of microgreen basil. Radiation with a combination of 100% red light with irradiation for 20 hours increased the chlorophyll and carotenoid content of basil microgreen.